(untitled) (Iraqi Journal of Civil Engineering, 2017)
Housing represents a major world wide problem, especially for developing countries. It is essential to construct suitable housing units that are appropriate for the continuing population increase. Many countries have applied construction (policies) that depended on the available material and human resources. These schemes aim at producing the greatest number of dwelling units that are suitable for the people who do not own units. The aim of this research is the scope of low cost dwelling units in general, and through the reduction of roofing cost. The objective of the research, Economical feasibility study for production precast units (ferro cement units) for roofs of low cost dwelling and compare the cost of the proposed system With other conventional roofing systems: roofing by (jack arching) and reinforced concrete. Fifteen units of Ferrocement with square shape and three different dimensions were cast and tested for load test, tensile strength, compressive strength and bending. The optimized dimensions were (750*750*20)mm and the capacity ranges from (13 to 17.7)KNM2.The cost of (1m2 ) of these units was (38292.4)I.DM2 while the cost of (1m2 ) reinforced concrete (58534.94(I.D and (51062.7) I.DM2 for (jack arching)